One phase voltage and current harmonic analysis / Wan Azlan Wan Hashim and Mohd Arman Adnan - Wan Hashim, Wan Azlan; Adnan, Mohd Arman (2005)
Harmonic is one of part in power quality issues that it has grown and it has been discussed as major issues. Command problem in harmonics analysis are voltage and current harmonies which creating harmonics distortion. Nowadays, linear and non linear load used widely around the world and it give all engineers concern for harmonics distortion especially in AC power system. In this project, the investigation about this problem will be done and it is involving voltage and current harmonics analysis, due to non linear loads application. From the analysis result, the passive filler will be designed to reduce the harmonics distortion and it also improved the quality of AC power. Our mission is to analyze the harmonics and the way how can we reduces it with the filter that we have describe below in the following chapter. The filter that will be used will be designed by ourselves if we can manage it.